A square tubular conducting polymer actuator for smart catheter application. Issue 4 (16th October 2019) - Zhao, Lei; Yang, Ying; Hu, Yimin; Li, Cheng; Wu, Yanxiao; Ren, Ming; Chen, Wei
Abstract: Flexible micro-catheter for minimally invasive medical diagnosis and therapy is highly desirable, but still a challenge. Here, an active interventional micro-catheter based on square tubular conducting polymer actuator is developed. This actuator is composed of two conducting polymer composite electrodes and a square tubular gel polymer electrolyte layer between the electrodes layer. To fabricate the square tubular gel polymer electrolyte layer, a simple, solution-based, gradual phase inversion technique was used. A high ionic conductivity and low tensile modulus Poly(vinylidenefluoride-co-hexafluoropropylene) (PVDF-HFP) square tube that could act as the actuator body and electrolyte layer to allow the actuator operate without the need of external ions was fabricated. Also, since the electrodes are supposed to be largely deformed under low voltage, which has great significance for the safe application of the catheter for the human body, conducting polymers with good electrical and mechanical properties are great choice for the catheter. Therefore, we developed a PEDOT:PSS/carboxylic SWCNT (SWCNT-COOH)/ionic liquid (IL) composite electrode film. With the addition of SWCNT-COOH and IL, the conductivity reached more than ten times higher than that of pristine PEDOT:PSS and the specific capacitance was three times higher than that of PEDOT:PSS film. Additionally, the stretchability and flexibility of the electrode film were highly enhanced because of the doping of IL. Due to the high electrical conductivity of composite electrode and low tensile modulus of actuator body, the obtained square tubular actuator can bend in two dimensions under a low voltage (∼1 V) in open air. A simulated vessel model was constructed and the square tubular actuator succeeded in real-time active bending and guiding, which will have broad application prospects in the interventional medicine field.